Anil agarwal reader 01 (New Delhi, 2007)
The Anil Agarwal Reader collects in three volumes some of his writings on the environment. They range from the 1990s to the early years of this decade. The volumes showcase the intensity and acuity with which he engaged with the dominant concerns of the times. They are an essential introduction to environmental questions, moving seamlessly between local, national and international perspectives.
Keywords: Environment